BERTEOLOGI SOSIAL DALAM KONTEKS RADIKALISME KEAGAMAAN PADA ERA MILENIAL - Ratna Saragih (Jurnal Teologi Cultivation, 2019)
AbstractReligious radicalism is not addressed in a natural and transparent way, soit is feared that there will be a destruction of socity/ cilivization (“something like the destruction of civilization”). The Purpuse of this study is to strive for social theology in the context of religious radicalism. And this research is a qualitative research with exploratory description method. From this research it was produced: Controlling crime, religious people are compassionate people, and pave the theology of contextual religions.Keywords: Theology, Social, Radicalism